Assessment of the influence on Hypsizygus marmoreus stem waste as a sustainable alternative to corn in Holdobagy geese dietary - Li, Guangquan; Liu, Yi; Wang, Xianze; Gong, Shaoming; Yang, Yunzhou; Wang, Cui; Wang, Huiying; He, Daqian (Frontiers in Sustainable Food Systems, 2023)
This study aimed to investigate the effects of substituting dietary corn with Hypsizygus marmoreus mushroom stem waste (HSW) in the diet of geese. The control group was fed with a basal diet (BD), and the other groups were fed the basal diet to which 12% (HSW12 group), 24% (HSW24 group), or 32% (HSW32 group) of HSW were added to replace the equivalent proportion of corn. The test lasted 28 days. The results showed that the average daily feed intake (ADFI) of the HSW12 and HSW24 groups at 35–49 d, and the HSW12 and HSW32 groups at 35–63 d, was significantly higher compared to the BD group (P<0.05). The average daily gain (ADG) of the HSW12 group was significantly higher than BD at 35–49 d (P<0.05), but there was no significant difference in the feed/gain (F/G) among the groups. The levels of serum total protein (TP), albumin (ALB), globulin (GLOB), glutathione peroxidase (GSH-Px), and catalase (CAT) in HSW24 group were significantly higher than those in the BD group (P<0.05). Total cholesterol (TC), triglycerides (TG), low-density lipoprotein cholesterol (LDL-C), and malondialdehyde (MDA) decreased significantly, and there were no significant differences in carcass traits and meat quality. As 24% HSW supplementation had the best overall effect on the growth performance, serum biochemical indicators, meat quality, and carcass traits of geese, gut microbiota analysis was only performed on this group. The microbiota α-diversity of the cecum and ileum did not differ significantly between the BD and HSW24 groups. Principal coordinate analysis (PCoA) indicated that the difference in the cecum was significant in the β-diversity (P<0.05). Short chain fatty acid-producing bacteria and decomposing protein and carbohydrate bacteria (Prevotella) were enriched in the cecum in the HSW24 group. Gut immune regulating and nutritional bacteria, Lactococcus and Bacillus, respectively, were enriched in the ileum in HSW24 group. Spearman’s analysis indicated that Bacillus, Prevotella, and Clostridium were positively associated with serum protein and lipid metabolism. These results indicate that 24% HSW substitution of corn could improve goose serum ALB and fat metabolism, and increase serum antioxidant capacity, which may becaused by the improvement of goose cecal microbiota.